Seconds to live [large type] - Sleeman, Susan (Homeland heroes, 2020)
"When cybercriminals hack into the U.S. Marshal's Witness Protection database and auction off personal details to the highest bidder, FBI Agent Sean Nichols begins a high-stakes chase to find the hacker. Trouble is, he has to work with U.S. Marshal Taylor Mills, who knows the secrets of his past, and the seconds are ticking down before someone dies"--Provided by publisher.